Off/On Amino-Functionalized Polyhedral Oligomeric Silsesquioxane-Perylene Diimides Based Hydrophilic Luminescent Polymer for Aqueous Fluoride Ion Detection - Sun, Mingxia; Liu, Houjing; Su, Yingying; Yang, Wenxi; Lv, Yi (Analytical chemistry (Washington), 2020)
Fluoride ion detection in water focuses much attention due to the serious healthy impact in human pathologies. For fluoride recognition, the chemical affinity between fluoride and silicon has been developed on the basis of the degradation mechanism. However, most fluorescent probes are the "turn off" type due to the aggregation of the degradational products. Herein, we first developed an "off-on" hydrophilic luminescent polymer composed of amino-functionalized polyhedral oligomeric silsesquioxane (AE-POSS) and perylene diimides (PDIs) for fluoride ion in water. The AE-PDI polymer was "turned off" because of the photoinduced electron transfer (PET) between PDI and AE-POSS, and then after reaction with F , the fluorescent emission could "turn on" obviously because the PET was blocked by the degradation of the cage. The PET from amino-POSS to PDI was proved by FL spectrum and energies of HOMO and LUMO orbitals. Si, F NMR, and H NMR titration, XRD, FTIR, size analysis, and ion chromatography were applied to demonstrate the degradation mechanism. These results indicated that the higher quantum yield could be obtained by introducing the amide group in the PDI and the products of AE-PDI polymer might exist in the form of complex compounds with partial condensation of organosiloxane. With high selectivity and sensitivity (detection limit of 16.2 ppb), this probe was successfully applied for F detection in actual water samples.